Availability Optimization Of Nidec Manufacturing Plant Using Markov Process - Sakshi Jaglan; Vinod Kumar (Revista Electronica de Veterinaria, 2024)
In the current work, Reliability Analysis the system parameters of the Nidec Manufacturing Plant using Markov Process has been optimisation. The goal of the present paper is to optimize input variables of the Nidec Manufacturing Plant to maximize framework availability. Nidec Manufacturing Plant contains six subsystems named as CNC machine (K), VMC machine (L), CNC hobbing machine (M), Induction hording machine (N), Grinding machine (O), and Polishing machine (P) so Nidec plant is a very complex system. All the subsystems are connected in series. In this paper, we have evaluated availability and reliability for the considered system by applying Markov process. The value of availability and reliability is decreased by increasing the time. Consistent state accessibility is accomplished by consuming normalizing condition.